The Influence of Personal Factors on Purchase Decisions for Fashion Products at CB Fashion Stores in Lhokseumawe - Ikramuddin Ikramuddin; Rizka Astuti; Mariyudi Mariyudi; Naufal Bachri; Juni Ahyar (Inovbiz: Jurnal Inovasi Bisnis, 2022)
This study aims to determine the influence of personal factors on purchasing decisions for fashion products at the CB Fashion Store in Lhokseumawe. The samples consisted of 100 respondents selected using a purposive sampling method. The data was collected by a questionnaire survey and analyzed using regression analysis. The results indicate that the variable of Age and Life Cycle Characteristics (X1), Job Characteristics and Income (X2), Lifestyle Characteristics (X3), and Personality Characteristics (X4) have a positive and significant impact on purchasing decisions for fashion products at CB Fashion Stores in Lhokseumawe. The findings have implications for establishing the concept of personality in purchase decision model.